Demonstração da qualidade de óleos lubrificantes básicos produzidos a partir do rerrefino em uma empresa na cidade de Manaus - AM - Pereira, Hyara da Cunha Sena (Universidade Federal do Amazonas, 2018)
The present study aims to characterize and evaluate the quality of basic lubricating oils produced in a re - refining process plant in the city of Manaus - AM. Lubricating oils play a key role in the evolution of the industry, which is always developing machines that work with higher yields and productivity, thus requiring lubricants with better performance that are of great importance for the oil industry and especially for the midstream follow-up the refining and re-refining processes. This activity is little known in the country and the refineries that perform it end up facing great challenges in the consumer market, for having the quality of their products judged inferior when compared to the fractions of interest coming from the first refining, although it is greatly encouraged by being the proper disposal and treatment of used and / or contaminated lubricating oils. In this way, this work is directed to describe the steps of re-refining operation, to analyze and control the quality of the oil produced from the determination of its physico-chemical properties and to compare the functionality of the re-refined basic oil with the first refining, according to the specifications in force by the National Petroleum Agency.